Pengaruh Model Pembelajaran Berbasis Masalah pada Materi Aritmetika Sosial terhadap Prestasi Belajar Matematika Siswa - I Putu Wahyu Paramartha; Sri Subarinah; Arjudin Arjudin; Nyoman Sridana (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to determine the effect of problem-based learning models on social arithmetic material on the achievement of mathematics learning for grade VII students of SMP Negeri 2 Lingsar for the 2021/2022 school year. This Quasi-Experimental Design research is designed by The Posttest Only Control Group Design. The population is all grade VII students of SMPN 2 Lingsar, as many as 278 students. Sample determination is carried out by the Cluster Random Sampling technique. Class VII.5 used a problem-based learning model with 31 students as an experimental class, and Class VII.9 used a direct learning model with 30 students as a control class. The data on the achievement of learning mathematics is obtained through the final test. The assumption tests in this study are the normality test and the homogeneity test. Data analysis in this study used descriptive statistical analysis and a t-test. The results showed that the average learning achievement of the experiment class was 79,10 greater than the average learning achievement of the control class, which was 70,23. In this study, the problem-based learning model had a moderate influence on 79% of the expectations of mathematics learning achievement of grade VII students